RNA-seq Transcriptome Response of Flax (Linum usitatissimum L.) to the Pathogenic Fungus Fusarium oxysporum f. sp. lini - Galindo-González, Leonardo; Deyholos, Michael K. (Frontiers in Plant Science, 2016)
Fusarium oxysporum f. sp. lini is a hemibiotrophic fungus that causes wilt in flax. Along with rust, fusarium wilt has become an important factor in flax production worldwide. Resistant flax cultivars have been used to manage the disease, but the resistance varies, depending on the interactions between specific cultivars and isolates of the pathogen. This interaction has a strong molecular basis, but no genomic information is available on how the plant responds to attempted infection, to inform breeding programs on potential candidate genes to evaluate or improve resistance across cultivars. In the current study, disease progression in two flax cultivars (CDC Bethune and Lutea), showed earlier disease symptoms and higher susceptibility in the later cultivar. Chitinase gene expression was also divergent and demonstrated and earlier molecular response in Lutea. The most resistant cultivar (CDC Bethune) was used for a full RNA-seq transcriptome study through a time-course at 2, 4, 8 and 18 days post-inoculation (DPI). While over 100 genes were significantly differentially expressed at both 4 and 8 DPI, the broadest deployment of plant defense responses was evident at 18 DPI with transcripts of more than 1,000 genes responding to the treatment. These genes evidenced a reception and transduction of pathogen signals, a large transcriptional reprogramming, induction of hormone signalling, activation of pathogenesis-related (PR) genes, and changes in secondary metabolism. Among these several key genes, that consistently appear in studies of plant-pathogen interactions, had increased transcript abundance in our study, and constitute suitable candidates for resistance breeding programs. These included: an induced RPMI-induced protein kinase (RIPK); transcription factors WRKY3, WRKY70, WRKY75, MYB113 and MYB108; the ethylene response factors ERF1 and ERF14; two genes involved in auxin/glucosinolate precursor synthesis (CYP79B2 and CYP79B3); the flavonoid-related enzymes chalcone synthase, dihydroflavonol reductase and multiple anthocyanidin synthases; and a peroxidase implicated in lignin formation (PRX52). Additionally, regulation of some genes indicated potential pathogen manipulation to facilitate infection; these included four disease resistance proteins that were repressed, indole acetic acid amido/amino hydrolases which were upregulated, activated expansins and glucanases, amino acid transporters and aquaporins, and finally, repression of major latex proteins.